Emergency Resuscitative Thoracotomy in the Combat or Operational Environment. (5th September 2018) - Monchal, Tristan; Martin, Matthew J; Antevil, Jared L; Bennett, Donald R; DeVries, William C; Zakaluzny, Scott; Ricca, Robert L; Tien, Homer; Mullenix, Philip S; Stockinger, Zsolt T
Abstract: Resuscitative thoracotomy has been extensively described in the civilian trauma literature and has a high mortality rate, due largely to the nature of the injuries leading to arrest. The survival rates are generally highest (10–30%) for penetrating truncal injuries and patients who arrive with vital signs and proceed to arrest or who have impending arrest. They are significantly lower (less than 5%) for blunt trauma victims, particularly those who arrest in the field or during transport (1% or less). In addition, the likelihood of survival with intact neurologic function is significantly lower than the overall survival rates, particularly for blunt trauma victims and for prehospital arrest.